A novel method for estimating transient thermal behavior of the wellbore with the drilling string maintaining an eccentric position in deep well operation. (25th December 2019) - Yang, Mou; Xie, Rongxuan; Liu, Xianming; Chen, Yuanhang; Tang, Daqian; Meng, Yingfeng
Highlights: A new method for estimating wellbore temperature in eccentric annulus was developed. Annulus temperature decreases with an increase of eccentric ratio of drill string. Fluid radial thermal gradient can be neglecting in developing numerical model. Simulation results from developed model were validated using field measured data. Abstract: An eccentric annulus is very common, caused by a change of hole-deviation angle and azimuth angle with well depth, leading to a difference in the heat transfer mechanism, compared with a concentric annulus. Based on the energy conservation principle, a rigorous transient heat transfer model in each region of wellbore and formation in the eccentric annulus was first established. The numerical model was validated by the field case. Combined with computational fluid dynamics software, the fluid flow regime and heat exchange mechanism in various eccentric annuluses were investigated. The results demonstrate that the annulus temperature gradually decreases with an increase in the eccentricity ratio of the drilling string, and the temperature difference between the concentric annulus and eccentric annulus of 0.9 is around 4 °C. Also, as the eccentricity ratio is elevated, fluid in the narrow gap is slowly heated; fluid in the wide gap is decreased due to a high flow rate carrying more formation heat to the wellhead. Most importantly, the maximal radial temperature difference in the wide gap under the various eccentric conditions is about 0.2 °C, and fluid radial thermal gradient could be neglected in the modeling process during the fluid circulation stage.